Attempted repair of chest wall injury following penetrating injury with surgical stabilization rib and autologous bone graft: A case report - Vincent E. Serapiglia; Krishna A. Patel; Jaya Sai V. Varre; Brian T. Dusseau; William B. DeVoe (Trauma Case Reports)
Rib fractures are one of the most common injuries following blunt trauma. When associated with penetrating trauma, the projectile velocity and immense energy transfer cause significant rib fracture displacement and fragmentation. As a result, these patients are potentially exposed to an even higher risk of complications compared to those seen in more simple rib fractures. Unfortunately, there is limited research regarding technical considerations for surgical stabilization of rib fractures (SSRF) in severely displaced rib fractures with bone loss following penetrating injury. We present the case of a 21-year-old male gunshot wound victim with severely displaced and comminuted rib fractures in which we utilized an autologous bone graft bridge during SSRF to enhance fracture unionization, chest wall stability, and cosmesis. Unfortunately, the bone graft failed to incorporate into surrounding tissue.